Advanced healthcare systems : empowering physicians with IoT enabled technologies - Balamurugan, S. (Shanmugam), 1985-; Saini, Rakesh; Bharti, Vishal; Chithaluru, Premkumar (Artificial Intelligence and Soft Computing for Industrial Transformation, 2022)
This book offers a complete package involving the incubation of machine learning, AI, and IoT in healthcare that is beneficial for researchers, healthcare professionals, scientists, and technologists. The applications and challenges of machine learning and artificial intelligence in the Internet of Things (IoT) for healthcare applications are comprehensively covered in this book. IoT generates big data of varying data quality; intelligent processing and analysis of this big data are the keys to developing smart IoT applications, thereby making space for machine learning (ML) applications. Due to its computational tools that can substitute for human intelligence in the performance of certain tasks, artificial intelligence (AI) makes it possible for machines to learn from experience, adjust to new inputs and perform human-like tasks. Since IoT platforms provide an interface to gather data from various devices, they can easily be deployed into AI/ML systems. The value of AI in this context is its ability to quickly mesh insights from data and automatically identify patterns and detect anomalies in the data that smart sensors and devices generate - information such as temperature, pressure, humidity, air quality, vibration, and sound - that can be really helpful to rapid diagnosis.